The effect of melatonin on glycoprotein levels and oxidative liver injury in experimental diabetes. Issue 3 (16th December 2022) - Ertik, Onur; Sener, Goksel; Yanardag, Refiye
Abstract: In this present study, the duration of melatonin (Mel) administered to diabetic rats was prolonged so as to examine its effects on the biochemical liver parameters of diabetic rats. In the experiment, Male Sprague Dawley rats were divided randomly into five groups; the control, diabetic + Mel, diabetic, diabetic + insulin, and diabetic + Mel + insulin. Diabetes mellitus was induced by administration of a single dose of streptozotocin (60 mg/kg) intraperitoneally and rats were given vehicle as a solvent for Mel every day for 12 weeks. In the diabetic + Mel group, diabetic rats were administered Mel (10 mg/kg/day) for 12 weeks to treat diabetes. The diabetic + insulin group were diabetic rats given insulin (6 U/kg) subcutaneously for 12 weeks. The diabetic + Mel + insulin rats received insulin and Mel at the same dose and time. At the end of the experiment, the animals were decapitated and liver tissues were taken. The protective effect of Mel on liver tissue of diabetic rats was investigated, total antioxidant status, total oxidant status, reactive oxygen species, oxidative stress index, adenosine deaminase, xanthine oxidase, paraoxonase 1, sodium/potassium ATPase, myeloperoxidase, γ‐glutamyl transferase, sorbitol dehydrogenase, tumor necrosis factor‐alpha, homocysteine, nitric oxide, glucose‐6‐phosphate dehydrogenase, and glycoprotein levels were determined in liver tissues. Treatment with Mel and/or insulin has been found to have a protective effect on biochemical parameters. The results showed that administration of Mel to diabetic rats prevented the distortion of the studied biochemical parameters of liver tissues.